Psychotherapeutic Journeys into the Spiritual World of Healing on the Wings of Gnawa Music: An Anthropological Study - Meryem Madili (Különleges Bánásmód, 2024)
From the sufferings their art was born, from the torture they lived in during their life as slaves their music was created. From the torturing tools used on them they created their own musical instruments. From their screams as slaves, they composed a new music with unique rhythms. Gnawa become a cultural phenomenon in Morocco. A sufi confrerie imploring God, the prophet and the saints to release them from slavery, torture and the sufferings they encountered. Their music is considered spiritual because it calls souls to join its magic. Gnawa plays a psychotherapeutic role in healing people from various diseases through the practices of syncretic rituals and the trance state they put the participants into. All of these elements music, dances and rituals converge and synthesize into an event called lila a rich ceremony in which the sick tormented by spirits could get healed. This paper examines the practices and impact of the lila ceremony on the community from a psychological point of view revealing each step of the collective healing process and methods as used in the rituals.